Creative Thinking Analysis, Motivation and Concept Mastery on Learning of Cooperative Discovery Model in Elementary School (Journal of Primary Education, 2018)
The reason to do this research is because the creative thinking ability, motivation and mastery concept still less than optimal. The purpose of this research is to analyze the improvement of creative thinking ability, motivation and mastery of students’ concepts through cooperative discovery learning model. This research is quantitative research and design experimental with nonequivalent control group. The population in this research is the fifth grade students’ of Rejosari 02 and Rejosari 03 elementary schools. The sample of this research is choosen by using purposive sampling technique. The are 5a obtained 51 students as a control class and class 5b, 50 students as an experimental class. The research instrument is in the form of tests of creative thinking ability, questionnaire of learning motivation and concept of mastery test. The hypothesis test using the N-gain test and independent sample t-test. The result showed as follows: (1) the improvement of students’ creative thinking ability taught by using cooperative discovery learning of, is in category and those who average are in medium category. (2) the improvement of students’ learning motivation that taught by using cooperative discovery learning is of 82.12 and that of conventional learning is of 76.69. (3) There is a difference in the mastery of students' concepts that taught by using cooperative discovery learning and the conventional learning. So it can be concluded that by using cooperative discovery learning are the students’ creative thinking, motivation and concept mastery higher than that of conventional learning. This research gives the implication that cooperative discovery learning is suitable to use in the fifth grade of elementary school to increase the students’ creative thinking, motivation and as.